Effect of Size and Drying Time on the Rehydration and Sensory Properties of Freeze-Dried Snails (Achatina achatina) - Matthew A. Achaglinkame; Eric Owusu-Mensah; Abena A. Boakye; Ibok Oduro (International Journal of Food Science)
Snails, a delicacy in most tropical communities, are highly perishable and seasonal. Employed preservative methods are highly temperature dependent, adversely affecting their nutritional value and sensory properties. This study was aimed at determining the effect of size and drying time on the rehydration and sensory properties of freeze-dried snails. Snails were sized into three categories with average weights: 7.59 g (quarter-sized), 14.41 g (half-sized), and 30.71 g (whole), and freeze-dried for 15, 20, and 25 h. The moisture content and percent rehydration of the dried samples were determined by standard methods and sensory properties assessed by an in-house panel of 30 using a 5-point hedonic scale. The moisture content of the fresh and freeze-dried samples ranged from 65.80 to 75.20% and 3.25 to 10.24%, respectively. Freeze-dried samples had higher percent rehydration (27 to 102%) than the control; smoked snails (21 to 32%). Size had a significant (P<0.05) effect on the rehydration ability of the samples with the half-sized and freeze-dried for 15 h samples having the highest. The freeze-dried samples generally had higher consumer preference than the control in all attributes assessed. The findings show that freeze-drying snails (approximate weight of 14.4 g) for 15 h could be a consumer-preferred alternative preservative method for extending the shelf life of snails.